Compost and Zinc Application Enhanced Production of Sweet Potatoes in Sandy Soil - Md. Sarwar, Jahan; Khairi, M; Nozilaudi, M (2016)
Composting releases nutrients in the less fertile soil to increase soil health for sustainable production of a crop. To investigate the effects of compost-and zinc (Zn)- induced growth and development of sweet potato, we measured different parameters of sweet potato. Different concentrations of Zn (0.0, 0.2, 1.5 and 3.0 ppm) were applied as a foliar spray to the plants with or without composting. Compost increased leaf area, chlorophyll content, relative water content in leaves, moisture content in the tuber, photosynthesis rate, numbers of tuber, the weight of tuber, ash, crude fiber and crude protein in tuber of sweet potato plants regardless of Zn application. Zinc concentration at 0.2ppm showed better results in the above parameters compared to the control and higher concentration of Zn. These results confirmed that composting might increase sandy soil health to sustain the production of sweet potato in sandy soil